Effects of ultrasound, radial extracorporeal shock waves, and electrical stimulation on rat bone defect healing. Issue 1 (22nd February 2021) - Inoue, Shota; Hatakeyama, Junpei; Aoki, Hitoshi; Kuroki, Hiroshi; Niikura, Takahiro; Oe, Keisuke; Fukui, Tomoaki; Kuroda, Ryosuke; Akisue, Toshihiro; Moriyama, Hideki
Abstract: Fractures associated with osteoporosis are a major public health concern. Current treatments for fractures are limited to surgery or fixation, leading to long‐term bedrest, which is linked to increased mortality. Alternatively, utilization of physical agents has been suggested as a promising therapeutic approach for fractures. Here, we examined the effects of ultrasound, radial extracorporeal shock waves, and electrical stimulation on normal or osteoporotic fracture healing. Femoral bone defects were created in normal or ovariectomized rats. Rats were divided into four groups: untreated, and treated with ultrasound, shock waves, or electrical stimulation after surgery. Samples were collected at 2 or 4 weeks after surgery, and the healing process was evaluated with micro‐CT, histological, and immunohistochemical analyses. Ultrasound at intensities of 0.5 and 1.0 W/cm 2, but not 0.05 W/cm 2, accelerated new bone formation. Shock wave exposure also increased newly formed bone, but formed abnormal periosteal callus around the defect site. Conversely, electrical stimulation did not affect the healing process. Ultrasound exposure increased osteoblast activity and cell proliferation and decreased sclerostin‐positive osteocytes. We demonstrated that higher‐intensity ultrasound and radial extracorporeal shock waves accelerate fracture healing, but shock wave treatment may increase the risk of periosteal callus formation. Abstract : Physical agents have been suggested as a promising therapeutic approach for fractures. Here, we examined the effects of ultrasound, radial extracorporeal shock waves, and electrical stimulation on normal or osteoporotic fracture healing. We demonstrated that higher‐intensity ultrasound and radial extracorporeal shock waves accelerate fracture healing, but shock wave treatment may increase the risk of periosteal callus formation.